SEJARAH SOSIAL MASYARAKAT DESA BELIMBING KABUPATEN TABANAN TAHUN 1966 – 2014 - Listiani, Ni Wayan; Suwitha, I Gede Putu; Asmariati, A. A Inten (Humanis; Volume 16. No. 2. Agustus 2016, 2016)
The Social History of  Belimbing Village is community to discuss rural social life relationship with agriculture, that began to develop tourism since the 1990s. Farm life after the new order known as the period of reforms have a better development. Seeing the development of Belimbing Village community today has undergone many changes in quality, especially after the reform. Belimbing village farming communities have started independently, no longer dependent on outside parties such as the need for fertilizers, pestitida, and marketing of agricultural products are no longer dependent on outside parties such as the middleman. Belimbing Village Community experience different penetration and other outside influences, so inevitably people do the adaptation, among others, by transforming themselves. Belimbing village which lies at the crossroads between Denpasar, Tabanan and Singaraja an open village, so it is easy to absorb the modernization process. Modernisation include changes in knowledge, attitudes, and skills, and this change is a positive impact on people's lives, especially since the reform.